A combined quantum mechanics and molecular mechanics study on nitrogen oxide adsorption/dissociation on a tungsten oxide surface. (1st April 2015) - Izadyar, Mohammad; Balgerdi, Rahim; Pourayoubi, Mehrdad
The kinetics and mechanism of the adsorption and dissociation of nitrogen monoxide (NO) into N2 and O2 molecules on a tungsten oxide nanocrystalline surface have been studied. Calculations were carried out using the framework of density functional theory (DFT) with the ONIOM method at the (B3LYP/LANL2DZ:UFF) level. In this study, four models of the dissociation have been proposed and investigated theoretically. Density of states (DOS) spectral analysis showed that the Fermi level is shifted to higher values and confirmed the effective interaction between the nanocrystal and adsorbate. The band gap is also reduced after adsorption. Quantum reactivity indices showed that the chemical hardness was reduced after adsorption, which corresponds to the reduction in band gap. The electronic chemical potential has been shifted to more positive values while the electrophilicity of the surface has been reduced, both after adsorption. These parameters predict that charge transfers to the surface. Considering the activation energy, the first and second proposed models provide the most probable route of NO decomposition. Finally, from a comparison between the decomposition and oxidation processes, it is confirmed that NO oxidation is preferred.